DNA sensing via the cGAS/STING pathway activates the immunoproteasome and adaptive T‐cell immunity. (13th March 2023) - Wang, Xinyuan; Zhang, Huabin; Wang, Yuqin; Bramasole, Laylan; Guo, Kai; Mourtada, Fatima; Meul, Thomas; Hu, Qianjiang; Viteri, Valeria; Kammerl, Ilona; Konigshoff, Melanie; Lehmann, Mareike; et al.
Abstract: The immunoproteasome is a specialized type of proteasome involved in MHC class I antigen presentation, antiviral adaptive immunity, autoimmunity, and is also part of a broader response to stress. Whether the immunoproteasome is regulated by DNA stress, however, is not known. We here demonstrate that mitochondrial DNA stress upregulates the immunoproteasome and MHC class I antigen presentation pathway via cGAS/STING/type I interferon signaling resulting in cell autonomous activation of CD8 + T cells. The cGAS/STING‐induced adaptive immune response is also observed in response to genomic DNA and is conserved in epithelial and mesenchymal cells of mice and men. In patients with idiopathic pulmonary fibrosis, chronic activation of the cGAS/STING‐induced adaptive immune response in aberrant lung epithelial cells concurs with CD8 + T‐cell activation in diseased lungs. Genetic depletion of the immunoproteasome and specific immunoproteasome inhibitors counteract DNA stress induced cytotoxic CD8 + T‐cell activation. Our data thus unravel cytoplasmic DNA sensing via the cGAS/STING pathway as an activator of the immunoproteasome and CD8 + T cells. This represents a novel potential pathomechanism for pulmonary fibrosis that opens new therapeutic perspectives. Synopsis: Immunoproteasomes are activated by interferons and involved in MHC class I‐mediated CD8 + T‐cell activation as part of antiviral immune responses. This study demonstrates that cytoplasmic DNA sensing by the cGAS/STING pathway induces immunoproteasome‐mediated activation of CD8 + T cells that may be involved in idiopathic pulmonary fibrosis. Sensing of intracellular mitochondrial and genomic DNA via the cGAS/STING pathway activates the immunoproteasome and MHC class I antigen presentation in human and murine epithelial cells and fibroblasts. cGAS/STING activation induces CD8 +  T cell adaptive immune responses in a cell‐autonomous manner. Immunoproteasomes and CD8 +  T cells are activated in lungs of patients with idiopathic pulmonary fibrosis. Abstract : The DNA‐sensing cGAS/STING pathway regulates immunoproteasome function and MHC class I antigen presentation to promote T‐cell activation that may underlie pathology of idiopathic pulmonary fibrosis.